Pseudo-Construction Errors in Solving Number Pattern Problems Based on APOS Theory - Tilawah, Hilwatut; Lestari, Nurcholif Diah Sri; Pambudi, Didik Sugeng; Susanto, Susanto; Suwito, Abi (UNNES JOURNAL, 2024)
The concept of mathematical material is still not fully embedded in students' schemes, this means that errors occur in constructing the concept. This research aims to describe the actual situation regarding pseudo-construction errors that occur at the APOS (Action, Process, Object, and Scheme) stages. This research involved 28 students in class VIII A of SMPN 2 Silo Jember as subjects through problem solving test to get an comprehensive information about occuring errors. Then by the purposive sampling and snowball sampling techniques, two subjects are choosen to explore in depth through interview. The data valiadation is guarantee through the member check process. Data analysis includie data condensation, data presentation, and concluding. The results of the research are that pseudo-construction errors occur at every stage of APOS which results in the concept not being fully constructed in the student's scheme. As a recommendation, developing a mathematics learning model based on APOS theory to minimize the error is needed such that the concepts will be well and completely constructed in students' schemes. Konsep materi matematika masih belum sepenuhnya tertanam dalam skema siswa. Hal ini menunjukkan bahwa terjadi kesalahan dalam mengkonstruk konsep. Penelitian ini bertujuan untuk menggambarkan atau mendeskripsikan keadaan yang sebenarnya terkait kesalahan konstruksi semu yang terjadi pada tahapan APOS (Aksi, Proses, Objek, dan Skema). Penelitian ini melibatkan 28 siswa kelas VIII A SMPN 2 Silo Jember sebagai subjek melalui tes pemecahan masalah untuk mendapatkan informasi komprehensif tentang kesalahan yang terjadi. Kemudian dengan teknik purposive sampling dan snowball sampling, dipilih dua subjek untuk dieksplorasi secara mendalam melalui wawancara. Validasi data dijamin melalui proses member check. Analisis data meliputi kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian yaitu kesalahan konstruksi semu terjadi disetiap tahapan APOS yang mengakibatkan konsep tidak terkonstruk dengan utuh dalam skema siswa. Sebagai rekomendasi, perlu dikembangkan model pembelajaran matematika berbasis teori APOS untuk meminimalkan kesalahan agar konsep-konsep dapat terkonstruksi dengan baik dan lengkap dalam skema siswa.